Synthesis of new 4,6-disubstituted-1,3-5-triazin-2-yloxy esters and N-hydroxyamides - Mikhaylichenko, Svetlana; Kvak, Olga; Dalili, Shadi; Zaplishny, Vladimir (European Journal of Chemistry, 2010)
A convenient method for synthesis of new sym-triazine ester and hydroxamate derivatives has been developed. Various reaction conditions were studied and optimized, and a series of new 1,3,5-triazine based esters and N-hydroxyamides were obtained with good yields (38-80%). The reaction between oxo-derivatives of 4,6-disubstituted-1,3,5-triazines and halogenated carboxylic esters derivatives using Cs2CO3 as a catalyst was found to be the most convenient method for 4,6-disubstituted-1,3,5-triazine-2-yloxy esters synthesis. These 1,3,5-triazin based esters served as precursors for the synthesis of 4,6-disubstituted-1,3,5-triazin-2-yloxy-N-hydroxybutanamides using solution of hydroxylamine hydrochloride in dry methanol and KOH at room temperature. Structures of the newly synthesized compounds were obtained by 1H NMR, 13C NMR, MS, IR spectral data and elemental analysis.